Constituintes químicos e atividade biológica dos organismos marinhos: Caulerpa mexicana, Bryothamnion triquetrum, Hypnea musciformis e Ircinia felix - Lira, Daysianne Pereira de (2014)
The Brazil is among the first 10 countries in the ranking of the world's biodiversity and to present one of the largest coastal areas in the tropical region of the world has awakened to the importance of marine products as a source of richness of our flora and as a source of unbeatable structural diversity of chemicals of various classes, able to build molecules of high structural complexity, with absolute chemo, regio and stereoselectivity constituents. Being aware that one of the most important aspects in bioprospeção flora and fauna is the knowledge about the chemical and pharmacological potential aquatic habitat found on the Brazilian coast in particular Paraiba coast, aimed to isolate and identify the chemical constitintes three species of algae : Caulerpa mexicana, Hypnea musiformis and Bryothamnion triquetrum; and a sponge: Ircnia felix, as well as evaluate their cytotoxic and antitumor activities, and partnerships to conduct assessment of the antinociceptive and anti-inflammatory activities of these products. Thus, by standard chromatographic and spectroscopic methods IR, 1H NMR and 13C and uni-dimensional, GC-MS, MALDI-MS and compared with literature values was possible to isolate and identify seven substances: a steroid and β-Sitosterol caulerpina one alkaloid from Caulerpa mexicana; Saringosterol one steroid and barbiturate 2,4,6 (1H, 3H, 5H)-pirimidinatriona, 5-ethyl-5-phenyl of Hypnea musciformis; one cholest-4-en-3-one steroid and phthalate Di-isobutilftalato of Bryothamnion triquetrum; and a derivative of N - [(4E)-3-hydroxy-1 - {[(sodiooxi) sulfonyl] oxy} non-2-en-4-yl] dotriacontanamida of Ircinia felix, first reported in the literature. The methanol extracts of Hypenea musciformis and Bryothamnion triquetrum showed high and low cytotoxicity, respectively, when evaluated their cytotoxicity in erythrocytes of Swiss mice. However, these same extracts did not exhibit cytotoxic activity against tumor cells of Ehrlich Ascitic. And so, through partnerships held was observed that extracts of Caulerpa mexicana and Bryothamnion triquetrum showed significant results in different models of inflammation and the bis-indole alkaloid, the major substance of Caulerpa mexicana in tumor models of inflammation and espamolítica activity showed significaivos results.